2019
DOI: 10.1002/ente.201900358
|View full text |Cite
|
Sign up to set email alerts
|

Solar Water Splitting under Neutral Conditions Using Z‐Scheme Systems with Mo‐Doped BiVO4 as an O2‐Evolving Photocatalyst

Abstract: The photocatalytic water‐splitting system ideally consists of just photocatalyst powder and water without any additives. Herein, improvement of water‐splitting activity under neutral conditions is achieved by applying Mo‐doping and cocatalyst‐loading to BiVO4 of an O2‐evolving photocatalyst in a Z‐scheme system with Ru‐loaded SrTiO3 doped with Rh as a H2‐evolving photocatalyst and a reduced graphene oxide as an electron mediator. The strategies are based on the idea that the Z‐schematic electron migration proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Bismuth vanadate (BiVO 4 ) is a potential oxide photocatalyst and photoanode working under visible light irradiation because of the narrow bandgap (∼2.4 eV) of the monoclinic scheelite structure. However, the quantum efficiency is limited by the low electrical conductivity, low hole transfer efficiency, and the fast recombination of photogenerated electrons and holes. The strategies of heterojunction formation and donor doping have been addressed to resolve these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Bismuth vanadate (BiVO 4 ) is a potential oxide photocatalyst and photoanode working under visible light irradiation because of the narrow bandgap (∼2.4 eV) of the monoclinic scheelite structure. However, the quantum efficiency is limited by the low electrical conductivity, low hole transfer efficiency, and the fast recombination of photogenerated electrons and holes. The strategies of heterojunction formation and donor doping have been addressed to resolve these issues.…”
Section: Introductionmentioning
confidence: 99%
“…17 Meanwhile, the average diameters of SrTiO 3 :Rh,La and BiVO 4 :Mo particles had been determined by SEM as 0.3-0.7 mm and 0.5-2 mm, respectively. 17,34 As a reference, the observed values of the specific surface area of SrTiO 3 :Rh and BiVO 4 particles, prepared according to the abovementioned synthetic processes, had been determined by BET as 2.6 m 2 g À1 and 1.8 m 2 g À1 , respectively, [35][36][37] suggesting that SrTiO 3 :Rh,La and BiVO 4 :Mo particles prepared in this study had similar values of specific surface area. The X-ray diffraction patterns for SrTiO 3 :Rh,La and BiVO 4 :Mo particles could be assigned to perovskite-type SrTiO 3 with cubic phase and seelite-type BiVO 4 with monoclinic phase, respectively (Fig.…”
Section: Characterization Of Hep and Oep Particlesmentioning
confidence: 58%
“…98 Catalysis Science & Technology Mini review Molybdenum and tungsten have thus been used frequently as efficient dopants for BiVO 4 . 99 As Regmi et al demonstrated, 100 copper is also used as a dopant for BiVO 4 . They used microwave-assisted hydrothermal synthesis to make Cu-doped BiVO 4 and found that it had higher photocatalytic activity than undoped BiVO 4 for degrading ibuprofen and methylene blue while inactivating Escherichia coli.…”
Section: Performance Improvement Methodsmentioning
confidence: 99%